Microbiome: A Tool for Plant Stress Management in Future Production Systems - Salme Timmusk; Luz E. de-Bashan (Stresses, 2022)
Climate change, due to the altered composition of the global atmosphere from the “greenhouse effect”, is one of the biggest challenges to agricultural production systems [...]